What you see may not be what you get! Simulate towards effective planning of pediatric intensive care unit - Thyagarajan, Sujatha; Gowda, Sindhu Malvel; Ginigeri, Chetan; Anupama, S.; Chinnadurai, R. (Frontiers in Pediatrics, 2022)
Aims and Objectives: To describe the application of low-cost inter-professional simulation over 4 phases in identifying structural, design issues, latent safety threats, test systems, processes and facilitate team training during the design of a new Pediatric intensive care unit (PICU). Materials and methods: Four-phase inter-professional simulation sessions involving clinical and non-clinical teams were conducted over a 3-month period in a corporate hospital during the designing of a new PICU. Low-cost resources such as floor tapes, low-tech manikins, reused sterilized consumables and actual patient beds and equipment were used for the in-situ simulation sessions. A plus-delta method of debriefing was done and changes agreed on consensus were implemented after each simulated session. Results: There were 10 simulation sessions conducted over 4 phases during the 3-month period of designing the PICU. The participants included 10 doctors from PICU and adult critical care, 25 critical care nurses, 12 members from the projects team, and 2 hospital administrators in various combinations. The first phase led to the re-design of workspace and clinical areas for better space utilization. The second phase required further revision to facilitate better mobility and facilities. In the third phase, the number of beds was reduced to 6 beds following the simulated drills involving the actual placement of patient cots and equipment. The fourth phase had thematic 5 simulated exercises involving the newly recruited clinical teams that enabled the identification of systems and process issues. Cognitive aids and video orientation of the setup, team training, and human factors training were addressed and the unit was open for patient care in a week. Conclusion: A phased inter-professional simulation exercise with low-cost resources can enable the identification of structural challenges, design issues, latent safety threats, test systems, processes, patient flow and facilitate team training during the design of a new PICU. Further studies are needed to understand the generalization of the study findings into designing PICU.